Effects of the corporate tax rates on firms' location selections through the trasfer pricing system - Toshiharu Ishikawa (European Regional Science Association (ERSA), 2014)
This paper analyzes effects of the corporation tax rates of countries on firms' location selections using the transfer pricing system. Reduction of transportation costs makes firms' production activities expand to across international borders. This expansion incurs harsh price competition among firms. In order to cope with this competition, firms fragment a production line into small processes to reduce production costs. The fragmented processes tend to move across some countries and locate at some places which are suitable to their production characteristics. The factories must be internationally connected each other in terms of intermediate materials and the related financial treatments. As a result, these factories handle the costs and the revenues arising from the internationally transferred intermediate goods by using the transfer price system. Furthermore, the firms, checking the corporate tax rates of countries, manipulate the transfer prices between their factories which are located in different counties to maximize their profits. This paper shows how the corporate tax rates of countries influence to a firms' location selections through working of the transfer price. Diffusion of the fragmented production processes incurs an increase in the production costs since a firm loses agglomeration economies which it enjoys by consolidating production processes at the same site. Hence it is very important to compare the changes in the benefits and the costs due to the distributing production processes. Incorporating the freight rates of intermediate goods and agglomeration economy into framework of analysis, this paper examines effects of the corporate tax rates of two countries on a firm's transfer price and factory's location. It is shown in this examination that change of the tax rate of a country clearly affects the transfer price but it does not alter factory's location in a country where transportation costs of intermediate goods are low: The influence of agglomeration economy to a firm's location selections varies according to a combination of the corporate tax rates between countries. Interestingly, there is a case that when the corporate tax rate in one country is raised, the tax revenue of the country increases, while the tax revenue of other country decreases by working of the transfer price.
Keywords: R30; 330; Transfer pricing; Firm's location; Corporation tax rates; Freight rates; Monopoly market; Chaotic phenomenon